EDUKASI GIZI SEIMBANG BALITA DAN MPASI-LOKAL â€œIKAN KEMBUNG COMOâ€ PADA KADER POSYANDU RW 021 SERUA CIPUTAT TANGERANG SELATAN - Erry Yudhya Mulyani; Yumelda Sari; Mariyana Widiastuti (Jurnal Abdi Insani, 2023)
Stunting is a national health problem with a prevalence of 21.6% from SSGI data in 2022, and this has not yet reached WHO standards. Reducing stunting is one of the targets of the Sustainable Development Goal (SDG) and the first of 6 targets of the Global Nutrition Targets program in 2025. Nutrition plays a role in the human life cycle, including nutrition in children-under-five. The golden age starts from 0-24 months where there is growth spurt and development. Therefore, this activity aims to provide basic knowledge to cadres about balanced nutrition and MPASI-Local Como Mackerel at Posyandu RW 021, Serua Ciputat, South Tangerang. The method used is lectures and discussions (focus group discussions). There are 17 cadres involved in this activity. This activity is divided into two, namely socialization through lectures and discussion through FGDs either in offline or online. Socialization activities were carried out for approximately 3 hours which were then continued with offline discussions about 1.5 hours. After that, by using the WhatsApp Apps (WA) media, education and discussion forums were continued. Some Posyandu cadres have served for more than 2 years and are generally housewives. There is an increase in mother's knowledge and attitude during education through socialization and discussion activities. Most of the mothers (more than 50.0%) were interested in the refresher material on balanced nutrition and local complementary foods. Therefore, it is necessary to carry out assistance and training to be able to develop local MPASI products that have high calories and protein as a follow-up effort.